General geology and hydrogeochemistry of groundwater at Terengganu river basin - Nur Amanina Rasyidah Suhaimi (2017)
A geological study has been conducted at the study area in order to update the geological map in scale 1:25 000 including the study of igneous, sedimentary and metasedimentary rocks that found in the study area. A base map in a scale 1:25 000 was prepared in order to traverse the study area that is compulsory in 5km² for the study. All the geological studies such as geomorphology, stratigraphy and structural geology have been observed. Generally, the groundwater of Terengganu River Basin is the main source of water for some residential area at Terengganu, the hydrogeochemical characteristics of groundwater in Terengganu River Basin has tendency of contamination by major chemical constituents and the trace element that were anticipated. A study of geochemical process could assist a lot in order to get the precise value of concentration of major chemical constituents and trace elements. All the major chemical constituent and trace element include Bicarbonate Bicarbonate (HCO₃ˉ), Chloride (Cl), Calcium (Cal), Magnesium (Mg), Sodium (Na), Potassium (K), Iron (Fe), Manganese (Mn), Copper (C) and Zinc (Zn) have been measured by using the Ion Chromatography (IC) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The physical parameters such as pH, Total Dissolved Solid (TDS), electric conductivity and salinity also been observed directly during the fieldwork sampling. All the value and the concentration could be obtained and analysed from this study. Besides, hydrogeochemical facies of the groundwater at the study area such as Alkali-HCO₃, Ca-Mg-HCO₃, Alkali-SO₄-Cl which are the type of groundwater were observed from this study.